Chemical Detoxification of Organomercurials1. Issue 32 (16th July 2015) - Banerjee, Mainak; Karri, Ramesh; Rawat, Kuber Singh; Muthuvel, Karthick; Pathak, Biswarup; Roy, Gouriprasanna
Abstract Organomercurials including methylmercury are ubiquitous environmental pollutants and highly toxic to humans. Now it could be shown that N‐methylimidazole based thiones/selones having an N‐CH2CH2OH substituent are remarkably effective in detoxifying various organomercurials to produce less toxic HgE (E=S, Se) nanoparticles. Compounds lacking the N‐CH2CH2OH substituent failed to produce HgE nanoparticles upon treatment with organomercurials, suggesting that this moiety plays a crucial role in the detoxification by facilitating the desulfurization and deselenization processes. This novel way of detoxifying organomercurials may lead to the discovery of new compounds to treat patients suffering from methylmercury poisoning.